2010
DOI: 10.1186/1742-2094-7-88
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 induces matrix metalloproteinase-9 and cell migration in astrocytes: roles of ROS-dependent ERK- and JNK-NF-κB pathways

Abstract: BackgroundTransforming growth factor-β (TGF-β) and matrix metalloproteinases (MMPs) are the multifunctional factors during diverse physiological and pathological processes including development, wound healing, proliferation, and cancer metastasis. Both TGF-β and MMPs have been shown to play crucial roles in brain pathological changes. Thus, we investigated the molecular mechanisms underlying TGF-β1-induced MMP-9 expression in brain astrocytes.MethodsRat brain astrocytes (RBA-1) were used. MMP-9 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 77 publications
(109 reference statements)
9
128
1
6
Order By: Relevance
“…The FASEB Journal x www.fasebj.org also secrete MMPs, application of an MMP inhibitor to the ACM may also inhibit MMPs produced by the tumor cells, thus confounding interpretation of the results. It has been found that TGF-b1 increases MMP production by astrocytes (48); however, the TGF-b treatment of astrocytes actually decreased the velocity of the subsequent ACMtreated tumor cells as compared to vehicle control-treated ACM. This suggests that MMPs are not the only, and potentially not the dominant, molecular mechanism at play in astrocyte-induced increased cell migration.…”
Section: Discussionmentioning
confidence: 97%
“…The FASEB Journal x www.fasebj.org also secrete MMPs, application of an MMP inhibitor to the ACM may also inhibit MMPs produced by the tumor cells, thus confounding interpretation of the results. It has been found that TGF-b1 increases MMP production by astrocytes (48); however, the TGF-b treatment of astrocytes actually decreased the velocity of the subsequent ACMtreated tumor cells as compared to vehicle control-treated ACM. This suggests that MMPs are not the only, and potentially not the dominant, molecular mechanism at play in astrocyte-induced increased cell migration.…”
Section: Discussionmentioning
confidence: 97%
“…The tyrosine kinase Src and phosphatidylinositol 3'-kinase (PI3K), and that phosphorylation of ERK1/2 can be inhibited by blocking TGF-βRI, Smad3, or the Nox oxidases (5,37). It is well established that ROS can activate MAPKs to exert functions in proliferation, differentiation and apoptosis (38,39), and ROS-dependent activation of ERK1/2 and JNK1/2 by TGF-β1 can induce MMP-9 expression and enzymatic activity, resulting in the promotion of cell migration in RBA-1 cells (40). Our results support the involvement of an additional signaling pathway, TGF-β1/ TGF-βRI/Smad2/ERK1/2/HIF-1α/GPx-1, in colorectal cancer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGF-β suppresses phosphatase and tensin homolog (PTEN) in glioma cells through enhanced miR10a/b expression (154). In patient samples, TGFB1I1 (TGF-β1-induced transcript 1) expression was found to be correlated with tumor grade, and activation of EMT pathways (152). In reaction to radiation treatment, the invasion capability of glioma cells is enhanced and TGF-β is upregulated.…”
Section: The Role Of Tgf-β In Glioma Cell Motilitymentioning
confidence: 99%